Roberto Brenes Mesén: su visión de la cultura y educación en la Costa Rica de principios del siglo XX - Isabel Carvajal, María (2008)
Nowadays, people argue about what parameters to follow on subjects like education and culture in Costa Rica. In the same way, this topic produced a great problem in philosophers and teachers in the first half of the twentieth century. This article pretends to approach Roberto Brenes Mesén’s way of thinking as well as his vision of culture and education.